Neglected Pediatric Osteochondral Fracture Dislocation of the Patella - Ta-Li Hsu; Shang-Ming Lin; Chih-Hung Chang; Tsung-Yu Lan (Case Reports in Orthopedics)
Pediatric osteochondral fracture dislocation of the patella is sometimes difficult to diagnose on the basis of physical examination or plain film radiography. Magnetic resonance imaging plays an important role in its early diagnosis, and early treatment can prevent damage to the articular cartilage as well as decrease the dislocation rate. Currently, many treatment choices have been reported with good results, but there is no consensus on which treatment option may lead to the best outcome. Herein, we describe the case of a 14-year-old girl with neglected osteochondral fracture dislocation of the patella. The outcome was optimal on the basis of a 2-year postoperative follow-up; thus, we believe that fixation with headless screws is a simple and effective method if the fracture fragment is large enough.